PEREMPUAN BERKEPRIBADIAN TANGGUH DAN DURHAKA ALQURAN “Kajian Tafsir Tematik” - E. Haikcal Firdan El-Hady (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2022)
ABSTRACT The Qur'an contains many sources of teachings that explain various presentations. One of the contents is in the form of stories that are presented. In the Qur'an there are several stories relating to pious women, these women are women who have tough personalities and there are also women who have a rebellious nature so that they are given a calamity by Allah SWT. because of its nature. With these stories, Muslim women should imitate and some are not exemplary by other Muslim women. However, nowadays it is increasingly difficult to find women who have strong personalities according to the stories in the Koran. Based on the description above, the author examines further about how the verses and interpreters analyze the story of women with strong personalities and dissidents in the Qur'an. This study aims to find out the verse and interpreter's analysis of the story of women with strong personalities in the Al-Quran, and to find out the verses and analysis of interpretations about the characteristics of women with strong personalities and rebellious personalities in the Al-Quran. The framework of thinking in this research, is based on the theory of Qaṣaṣ Al-Quran in the study of 'ulūm Al-Quran and also the theory of tough personality in the study of psychology. The author collects verses relating to stories about women with strong personalities, analyzes the interpretations of commentators on verses relating to research studies, and categorizes the results of the analysis of interpretations of verses relating to stories and their wisdom, as well as factors that influence tough personality and tough personality characteristics. This writing is (Library Research), ie all the materials needed are sourced from written materials related to the topics discussed. And using the Maudhu'i Tafsir method, as well as other related references as secondary sources. Based on the results of the author's research, there are four stories of women with strong personalities in the Koran, namely the story of Maryam, Asiyah, Ratu Balqis, the wife of Prophet Lut and the wife of Noah. The five stories have lessons that all Muslim women should emulate. Factors that influence storytellers to have strong personalities are self-concept, way of thinking, social behavior, family and education. The characteristics of women with strong personalities based on the commentators are those who have strong monotheism, piety to Allah, sincerity and pleasure in Allah's provisions, receive good education, maintain self-purity, have good ethics, have sharpness of mind, are compassionate and have a rebellious and rebellious temperament. which we should not emulate. We just need to take a lesson from this story. Keywords: Qaṣaṣ Al-Quran, Personality, Personality tough and disobedient in the Al-Quran. ABSTRAK Al-Quran mengandung sumber ajaran yang banyak menjelaskan beragam penyajian. Salah satu kandungannya yaitu berupa kisah-kisah yang dipaparkan. Dalam Al-Quran ada beberapa kisah yang berkenaan dengan perempuan shaleh, perempuan tersebut merupakan perempuan yang memiliki kepribadian tangguh dan adapula perempuang yang memiliki sifat durhaka sehingga diberi musibah oleh Allah SWT. karena sifatnya. Dengan kisah-kisah tersebut, sudah seharusnya untuk diteladani oleh perempuan muslim dan ada juga yang tidak patut dicontoh oleh wanita muslim lainnya. Akan tetapi, saat ini semakin sulit menemukan perempuan-perempuan yang memiliki kepribadian tangguh yang sesuai dengan kisah dalam Al-Quran. Berdasarkan uraian diatas, penulis meneliti lebih jauh tentang bagaimana ayat dan analisis penafsir mengenai kisah perempuan berkepribadian tangguh dan pembangkang dalam Al-Quran. Penelitian ini bertujuan untuk mengetahui ayat dan analisis penafsir mengenai kisah perempuan berkepribadin tangguh dalam Al-Quran, dan untuk mengetahui ayat dan analisis penafsiran mengenai karakteristik perempuan berkepribadian tangguh dan berkepribadian durhaka dalam Al-Quran. Kerangka berfikir pada penelitian ini, berdasar pada teori Qaṣaṣ Al-Quran pada kajian ‘ulūm Al-Quran dan juga teori kepribadian tangguh pada kajian psikologi. Penulis mengumpulkan ayat-ayat yang berkenaan dengan kisah-kisah mengenai perempuan berkepribadian tangguh, menganalisis penafsiran dari para mufassir terhadap ayat-ayat yang berkenaan dengan kajian penelitian, dan mengkategorisasikan hasil analisis dari penafsiran mengenai ayat yang berkenaan dengan kisah beserta hikmahnya, serta faktor yang mempengaruhi kepribadian tangguh dan karakteristik kepribadian tangguh. Penulisan ini bersifat (Library Research), yakni semua bahan yang dibutuhkan bersumber dari bahan-bahan yang tertulis yang berkaitan dengan topik yang dibahas. Dan menggunakan metode Tafsir Maudhu’i,dan juga referensi lain yang berkaitan sebagai sumber sekunder. Berdasarkan hasil penelitian penulis, kisah perempuan berkepribadian tangguh dalam Al-Quran itu ada empat kisah yaitu kisah Maryam, Asiyah, Ratu Balqis Istri Nabi Luth dan Istri Nabi Nuh. Kelima kisah memiliki hikmah yang harus diteladani oleh semua perempuan Muslim. Faktor yang mempengaruhi pelaku kisah memiliki kepribadian tangguh adalah konsep diri, cara berfikir, perilaku sosial, keluarga dan pendidikan. Adapun Karakteristik perempuan berkepribadian tangguh berdasarkan para mufassir adalah yang memiliki tauhid yang kuat, taqwa terhadap Allah, ikhlas dan ridha terhadap ketetapan Allah, menerima pendidikan yang baik, menjaga kesucian diri, beretika baik, memiliki ketajaman berfikir, penyayang dan memiliki perangai yang durhaka serta pembangkang yang tidak patut kita contoh. Cukup kita ambil hikmah dari kisa tersebut. Kata Kunci : Qaṣaṣ Al-Quran, Kepribadian, Kepribadian tangguh dan durhaka dalam Al-Quran.